Analysis of the Influence of the Ponot Waterfall Tourist Attraction on the Village Economy in Improving the Welfare of Households in Tourist Villages in Asahan Regency - Titah Enjelina Manurung; Rahmad Sembiring; Andria Zulfa (International Journal of Economics and Management, 2026)
This study aimed to analyze the effect of the tourist attraction on the village economy and household welfare, as well as to analyze the role of the village economy as an intervening variable in the Ponot Waterfall Tourism Village, Asahan Regency. This study used a quantitative approach with an associative research design. The method used was path analysis. The population in this study consisted of all residents of Tangga Village, totaling 1,950 people. The research sample consisted of 95 respondents who were determined using a purposive sampling technique, with the criteria of residents aged over 17 years and working in the tourism sector or owning micro, small, and medium enterprises. Data were collected by distributing questionnaires using a Likert scale. The data analysis techniques used included descriptive analysis, data quality testing, classical assumption testing, path analysis, and hypothesis testing with the assistance of SPSS version 24.0. The results showed that the tourist attraction had a positive and significant effect on the village economy, with a regression coefficient of 0.797 and a significance value of 0.000. The tourist attraction also had a positive and significant effect on household welfare, with a regression coefficient of 0.596 and a significance value of 0.000. The village economy had a positive and significant effect on household welfare, with a regression coefficient of 0.319 and a significance value of 0.000. However, the tourist attraction did not have a significant effect on household welfare through the village economy because the indirect effect value of 0.254 was smaller than the direct effect value of 0.596. These findings indicated that the existence of Ponot Waterfall provided greater direct benefits for improving household welfare than through the village economy pathway.